Millennials’ Perceptions of the Belis Tradition in East Nusa Tenggara: A Foucauldian Discourse Analysis of Conversations on X (Twitter) - Gesiradja, Asriyanti Saputri; Habsari, Sri Kusumo; Rais, Wakit Abdullah (Universitas Andalas, 2025)
This research explores the perceptions of the millennial generation of the belis tradition in Nusa Tenggara Timur (NTT) on social media, particularly Twitter. Belis is a traditional dowry practice in East Nusa Tenggara, deeply rooted in cultural significance as a symbol of respect, social recognition, and the familial alliance between the bride and groom’s families. The belis tradition has recently faced scrutiny from the millennials, who question its relevance in the modern era. This research employs qualitative analysis, drawing on primary data from tweets featuring the hashtag #TradisiBelisNTT. These tweets were examined through Foucauldian Discourse Analysis (FDA) following the six stages as outlined by Willig (2008): (1) Discursive Construction, (2) Discourse, (3) Action Orientation, (4) Positioning, (5) Practice, (6) Subjectivity. The findings suggest that belis is frequently perceived as an economic burden for men, hindering financial equality in marriage and prompting individuals to seek alternatives arrangements. The discourse as expressed in X reveals intricate power dynamics, as the millennial challenges traditional cultural norms and calls for reform in more inclusive and equitable cultural practices. The findings highlight the tension between preserving heritage and advocating for change, offering insights into how digital spaces facilitate dialogue on cultural reform.